Dermatologic manifestations and diagnostic assessments of the Ehlers-Danlos syndromes: a clinical review - Doolan, Brent; Lavallee, Mark; Haußer-Siller, Ingrid; Pope, F. Michael; Seneviratne, Suranjith L.; Winship, Ingrid M.; Burrows, Nigel P. (Journal of the American Academy of Dermatology, 2023)
Background - The Ehlers-Danlos syndromes (EDSs) comprise a group of connective tissue disorders that manifest with skin hyperextensibility, easy bruising, joint hypermobility and fragility of skin, soft tissues, and some organs. A correct assessment of cutaneous features along with the use of adjunct technologies can improve diagnostic accuracy. - Objectives - To systematically review the cutaneous features and adjunct investigations of EDS. - Methods - A search of PubMed and Web of Science for EDS-related cutaneous features and additional investigations was undertaken from publication of the 2017 International Classification of EDS until January 15, 2022. - Results - One-hundred-and-forty studies involved 839 patients with EDS. The EDS female-to-male ratio was 1.36:1 (P < .001). A high prevalence of skin hyperextensibility, bruising, and soft skin were noted. Most patients with vascular Ehlers-Danlos syndrome showed venous visibility, skin fragility, and acrogeria. Classical EDS showed subcutaneous spheroids and molluscoid pseudotumours. In patients that underwent skin biopsies, only 30.3% and 71.4% showed features suggestive of EDS using light microscopy and transmission electron microscopy, respectively. - Limitations - Retrospective study and small cases numbers for some EDS-subtypes. - Conclusions - An accurate clinical diagnosis increases the chances of a molecular diagnosis, particularly for rarer EDS subtypes, whilst decreasing the need for genetic testing where there is a low clinical suspicion for a monogenic EDS-subtype.